Case Report: Functional Investigation of an Undescribed Missense Variant Affecting Splicing in a Patient With Dravet Syndrome - Sparber, Peter; Mikhaylova, Svetlana; Galkina, Varvara; Itkis, Yulia; Skoblov, Mikhail (Frontiers in Neurology, 2021)
Pathogenic variants in the SCN1A gene are associated with a spectrum of epileptic disorders ranging in severity from familial febrile seizures to Dravet syndrome. Large proportion of reported pathogenic variants in SCN1A are annotated as missense variants and are often classified as variants of uncertain significance when no functional data are available. Although, loss of function variants are associated with a more severe phenotype in SCN1A the molecular mechanism of single nucleotide variants are often not clear and genotype-phenotype correlations in SCN1A-related epilepsy remains uncertain. Coding variants can affect splicing by creating novel cryptic splicing sites in exons or by disrupting exonic cis-regulation elements crucial for proper pre-mRNA splicing. Here we report a novel case of Dravet syndrome caused by an undescribed missense variant c.4852G>A (p.(Gly1618Ser). Using midigene splicing assay we demonstrated that the identified variant is in fact splice-affecting. To our knowledge this is the first report of functional investigation of a missense variant affecting splicing in Dravet syndrome.